2011
DOI: 10.1159/000328200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-Like Receptors 2, 4 and 9 in Patients with Guillain-Barré Syndrome

Abstract: Objective: A myriad of transcription factors and inflammatory cytokines have been described to participate in the pathogenesis of Guillain-Barré syndrome (GBS). However, the innate immunity components – Toll-like receptors (TLRs) – have never been explored in this disease. We therefore investigated the expression of TLR2, 4 and 9 in the peripheral circulation of GBS patients as well as healthy controls. Methods: Twenty-one GBS patients and 21 healthy donors participated in this study. Peripheral blood mononucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 59 publications
3
21
0
Order By: Relevance
“…Patients with GBS were divided into two groups (mild and severe) according to their clinical manifestation, and their mRNA levels were compared using Student's t-test. In accordance with the findings of Wang et al (19), the results of the current study demonstrated the same trend of alterations between TLR2, TLR4 and NF-κB mRNA and the condition of the patients with GBS. However, no significant difference was identified in MyD88 mRNA levels between patients with mild and severe GBS.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Patients with GBS were divided into two groups (mild and severe) according to their clinical manifestation, and their mRNA levels were compared using Student's t-test. In accordance with the findings of Wang et al (19), the results of the current study demonstrated the same trend of alterations between TLR2, TLR4 and NF-κB mRNA and the condition of the patients with GBS. However, no significant difference was identified in MyD88 mRNA levels between patients with mild and severe GBS.…”
Section: Discussionsupporting
confidence: 93%
“…In patients with GBS, Wang et al (19) found that TLR2, TLR4 and TLR9 mRNA levels were significantly increased. In accordance with the results of studies using the murine EAN model, it was suggested that TLR2, TLR4 and TLR9 may be involved in the pathogenesis of GBS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data regarding expression of TLR2 in GBS is very limited. So far, one study showed significantly elevated TLR2 expression in sciatic nerves during GBS 36 . An increased expression of TLR2 had been shown in synovial tissues of patients with RA 37 .…”
Section: Discussionmentioning
confidence: 99%